2019
DOI: 10.1101/847301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Reissner Fiber is Highly Dynamic in vivo and Controls Morphogenesis of the Spine

Abstract: SummarySpine morphogenesis requires the integration of multiple musculoskeletal tissues with the nervous system. Cerebrospinal fluid (CSF) physiology is important for development and homeostasis of the central nervous system and its disruption has been linked to scoliosis in zebrafish [1, 2]. Suspended in the CSF is an enigmatic glycoprotein thread called the Reissner fiber, which is secreted from the subcomissural organ (SCO) in the brain and extends caudally through the centr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…In rpgrip1l ∆/∆ , the RF fails to be maintained at the onset of scoliosis. Given that SCO-spondin mutants develop spine deformities [31], the loss of the RF in rpgrip1l ∆/∆ juveniles is a likely cause of scoliosis appearance.…”
Section: Discussionmentioning
confidence: 99%
“…In rpgrip1l ∆/∆ , the RF fails to be maintained at the onset of scoliosis. Given that SCO-spondin mutants develop spine deformities [31], the loss of the RF in rpgrip1l ∆/∆ juveniles is a likely cause of scoliosis appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence based on the labeling of SCO-spondin-GFP have revealed that the Reissner fiber in vivo is dynamic as well as straight as an arrow [47], which suggests that the fiber is under high tension in vivo. Given the dimensions of the central canal in living larvae (typically 10 µm by 9 µm) compared to the height of CSF-cN apical extensions (typically 3-5 µm) and the very thin diameter of the fiber (about 200 nm), it is conceivable that at rest, the thin RF could sit in the center of the central canal away from CSF-cN apical extension.…”
Section: How Can the Rf And Csf-cns Interact To Sense Spinal Curvature?mentioning
confidence: 99%
“…Furthermore, mutants for a receptor of the urotensin related peptides, which are solely produced by CSF-cNs in the spinal cord, exhibit a torsion of the spine, reminiscent of adolescent idiopathic scoliosis [9]. Finally, a recent report indicated that hypomorphic mutations in the scospondin gene induce 3D deformation of the spine [47]. Altogether, recent studies indicate that sensory neurons contacting the cerebrospinal fluid together with the Reissner fiber may contribute to the generation and maintenance of the shape of the spine.…”
Section: Relevance For Development Of Body Axis and Spinementioning
confidence: 99%
“…We then took advantage of the asynchrony in scoliosis onset to correlate, at a given stage, cilia defects at different levels of the CNS cavities with the spine curvature status (straight or curved) of rpgrip1l -/juveniles. We analyzed cilia defects in three CNS regions implicated in scoliosis appearance: the spinal cord central canal (since scoliosis develops in the spine), the forebrain choroid plexus (fChP) whose cilia defects have been associated to scoliosis in katnb1 -/fish (18) and the subcommissural organ (SCO), which secretes SCO-spondin whose absence leads to scoliosis (5,11).…”
Section: Defects At Sco Level Correlate With Scoliosis Appearance At ...mentioning
confidence: 99%
“…Cilia-driven movements of the cerebrospinal fluid (CSF) are involved in zebrafish axis straightness, both in embryos and juveniles (4,9) and are tightly linked to the assembly and maintenance of the Reissner fiber (RF), a SCO-spondin polymer secreted by the subcommissural organ (SCO) and running down the brain and spinal cord CSF-filled cavities (10). RF loss at embryonic stage in null sspo mutants is lethal while its loss at juvenile stage in hypomorphic sspo mutants triggers scoliosis with full penetrance (5,10,11). Signaling downstream of the RF in embryos implicates Urp1 and Urp2, two neuropeptides of the Urotensin 2 family expressed in ventral CSF-contacting neurons (CSF-cNs), which trigger dorsal muscle contraction in embryos and larvae (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%